Evaluation of the Use of Antihypertensive Drugs in Outpatients at Bandar Lampung Private Hospitals - Natalia, Lusia; Saputri, Gusti Ayu Rai; Wijaya, Satria (CV. Publikasi Indonesia, 2025)
Hypertension is one of the diseases that always receives the world's attention because it is the largest cause of morbidity globally. The main problem related to hypertension is the inaccuracy of prescribing antihypertensive drugs that often occurs in developing countries such as Indonesia. This study aims to evaluate the use of antihypertensive drugs in outpatients at Bandar Lampung Private Hospital. The study used a non-experimental descriptive quantitative method with a retrospective approach based on the medical records of hypertension patients for the period March-May 2024 using the JNC 8 guideline. The research sample was 100 hypertensive patients who met the inclusion and exclusion criteria. The results showed that the characteristics of patients were dominated by women (58%), age >60 years (48%), and hypertension of degree 1 (73%). The evaluation of the accuracy of the use of antihypertensive drugs showed the correct dosage of 165 patients (91%), the correct disease indication of 100 patients (100%), the correct selection of drugs for 100 patients (100%), the correct diagnosis of 100 patients (100%), the correct way of administering 181 drugs (100%), and the right time interval for giving 172 patients (95.03%). The most drug combination was ACEI + CCB (18%) with amlodipine 10mg as the most commonly used drug (19.34%). It can be concluded that the use of antihypertensive drugs at Bandar Lampung Private Hospital has shown a high level of rationality on most of the evaluation parameters.